A small-flowered Cyrtochilum (Oncidiinae) from Colombia - Ordóñez-Blanco, Juan Camilo (2022)
A new species of Cyrtochilum from the Cordillera Oriental range in the department of Cundinamarca, Colombia, is described, illustrated, and compared with C. suarezii and C. parviflorum. The new species is easily distinguished by its broadly elliptic to sub–rhomboid lip with two short rounded simple calli on the lip, ornamented with short papillae at the base.